ANALYSIS OF THE APPLICATION OF PERSONAL PROTECTIVE EQUIPMENT IN THE WELDING INDUSTRY - Egi Suryana; Sulaeman Deni Ramdani (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
The welding industry is one of the informal workplaces at risk of accidents and occupational diseases. Workers can be directly exposed to foreign matter or radiation from visible rays and sparks from the welding process during the welding process. This is a problem for people who are engaged in the profession of welding workers. This study aimed to analyze the application of personal protective equipment used by workers in the welding industry. This research is classified in the type of survey research and data collection techniques by observation, interviews, and questionnaire distribution. The subjects of the study were all workers in the welding workshop of Kec. Bayah welding totaling 30 people using random sampling techniques. The research path consists of 3 stages: preparation, data exploration in the field, and analysis of findings. Data analysis using percentages. Based on the analysis of the use of personal protective equipment in 6 welding workshops, Bayah has 57% in the good category and 33% in the less category. As for the analysis of each indicator, the most significant percentage of use in welding glasses is 76%, and the lowest percentage of skin protection is 56%. This shows that the level of concern of each worker is not balanced towards using all personal protective equipment in the welding process, which can cause very vulnerable work accidents.